MANAJEMEN TAHFIDZ QUR‘AN MELALUI PROBLEM BASED LEARNING - Milahtul Latifah (Al-Mubin, 2019)
Tahfidz Qur‘an Management through Problem-Based Learning of Muraja‘ah. The approach of this study is qualitative research with the type of field research. The respondents are determined through purposive sampling and data collection techniques used are observation, interviews, and documentation. The data are analyzed by reducing data, describing data, and drawing conclusions. There are also some analysis that use the legal approach of Jost 1) The management of the Qur‘anic tahfidz with analysis self-management, time, and responsibilities of memorizing the Qur'an. While the self-management by maximizing effort and strong determination, time management by taking benefit of time as good as possible, and self-awareness as memorizers of the Qur'an to remain consistent with the goal of the hufadz. 2) The application of the Problem -Based Learning method starts from the phenomenon of santri An-Nasuchiyyah who has problems in memorizing the Qur'an of the very fundamental problems, i.e.: forgetfulness, decreased enthusiasm, unable to manage effective time, the similarities in some verses, sleepy when memorizing, easy to despair, difficult to concentrate while being lazy. 3) While the effective Muraja‘ah model is muraja‘ah which is consistent in time and quantity